AO Reconstruction Plate as Buttressing for Greater Trochanter in Hemiarthroplasty Procedure - Luthfi Hidayat; Aditya Fuad Robby Triangga; Rahadyan Magetsari (The Hip and Knee Journal, 2022)
INTRODUCTIONThe trend of intertrochanter fractures has gradually increased leading to a high frequency of difficulties and damage as the result of the increased age and risk factors. Accordingly, the aim of stable fixation in these fractures is designed with appropriate surgical procedures and patient care. The contribution of a stable fixation is due to several considerations including fracture shape and assurance, bone quality, comminution pattern, implant choice, and surgical technique. This study aimed to assess the functional outcomes of the patients with an intertrochanteric fracture who underwent hemiarthroplasty with AO recon as buttressing.MATERIALS AND METHODSThis was a case series study conducted in Gadjah Mada University Academic Hospital in Yogyakarta from July 2017 to August 2018. Patients with Evans unstable intertrochanteric femoral fractures who underwent simultaneous bipolar hemiarthroplasty and fixation with AO reconstruction plate and SS wire as buttressing were evaluated. Pre and postoperative radiographs, postoperative Visual Analog Scale (VAS) score, walking ability using Harris Hip Score (HHS), and Lower Extremity Functional Score (LEFS) were the outcome parameters.RESULTSA total of 6 patients, 4 of whom were male with an average age of 81 years old were included in this study. All the mechanisms of injury were low-energy trauma. The mean VAS score was decreased, from 7 pre-operatively to 1.5 post-operatively at final follow-up (p-value 0.05). The patients had a mean HHS of 82.5 and a LEFS mean of 56.7.CONCLUSIONButtress plate fixation using an AO reconstruction plate for trochanteric fracture following bipolar hemiarthroplasty resulted in a good functional outcome.